The Truth Is Jesus Christ In The Gospel Of John On The Approach Of Popper’s Falsification - Khoe Yao Tung (Theological Journal Kerugma, 2021)
Many attempts to defend the concept of a Christian understanding of the Truth (ἀλήθεια) especially in the Gospel of John. To defend the Christianity concept of truth, believe The Truth is Jesus Christ himself. Secular scholars attempt to ruin this concept with many theories and principles. They have been continuing to reject this epistemology based on the philosophy of science and questioning what is the Truth and what is the connection with Jesus Christ. To defend this concept, an approach of Karl Popper’s falsification theory is used to justify the truth is Jesus Christ Himself in the Gospel and letters of John.